On the Dynamics of the Weak Fréedericksz Transition for Nematic Liquid Crystals (Communications in Computational Physics, 2020)
We propose an implicit finite-difference method to study the time evolutionof the director field of a nematic liquid crystal under the influence of an electric fieldwith weak anchoring at the boundary. The scheme allows us to study the dynamicsof transitions between different director equilibrium states under varying electric fieldand anchoring strength. In particular, we are able to simulate the transition to excitedstates of odd parity, which have previously been observed in experiments, but so faronly analyzed in the static case.